Stromal cells control soluble material and cellular transport in lymph nodes - Bajénoff, Marc (Frontiers in Immunology, 2012)
Lymphocytes continuously patrol the secondary lymphoid organs (SLOs) of mammals in search for their cognate antigens. SLOs are composed of leucocytes ( 95%) and lymphoid stromal cells ( 5%) that form the structural framework of these organs. These sessile cells have been considered for decades as inert elements of the immune system. This simplistic view has dramatically changed in recent years, when it was discovered that these architectural cells are endowed with immuno-regulatory functions. Lymph nodes (LNs) are located at the interface between the blood and lymphatic systems, thus allowing tissue-derived antigen/antigen presenting cells (APCs) to gather with blood-derived lymphocytes. As a typical LN contains 10 million of tightly packed cells, this accumulation of immune cells and information is probably not sufficient to foster the rare cellular interactions mandatory to the initiation of adaptative immune responses. Herein, I review some of the stromal cells physicochemical properties that are used to transport and guide immune cells and soluble molecules within LNs.